Farm to plate: School feeding catalysing investments in high iron bean value chain in Tanzania - Radegunda, Kessy; Fungo, Robert; Kalemera, Sylvia Monica; Kamanda, Josey; Machini, Justin; Mdachi, Mary; Mbiu, Julius; Nestory, Shida; Ubwe, Rose Matiko; Kasubiri, Fadhili Salum; Onyango, Patricia; Rubyogo, Jean-Claude (International Center for Tropical Agriculture, 2021)
Adequate nutrition is essential for schoolchildren’s health and wellbeing. Most children who benefit from school feeding programmes could already be nutrient deficient, vulnerable or at risk. These children rely heavily on such programmes because these could either be the only meal they consume in the day. In response to the high prevalence rates of malnutrition, to maximize the impact of investments on negative nutrition outcomes for women and children, multi-sectoral interventions are proposed as long-term sustainable approaches to address malnutrition in Africa (Garrett et al., 2011). Anticipating the release of HIB varieties in 2018, by the Tanzania Agriculture Research Institute (TARI) in collaboration with PABRA, the two organizations co-developed an approach to promote use and consumption of high iron beans (HIBs) in schools and surrounding communities. The approached used a multi-stakeholder approach consisting of: Local Government Authorities (LGAs), schools, entrepreneurs (grain traders, food processors), inputs suppliers (seeds and agro inputs) and end-users.